Use of Apple Snails (Pomacea canaliculata) as a Source of Fatty Acids in Feed Towards the Performance, Blood Cholesterol and Cholesterol Levels in Alabio Duck (Anas platyrhinchos borneo) Meat and Eggs - Subhan , Ahmad; Yuwanta, Tri; Zuprizal; Supadmo (International Journal of Poultry Science, 2014)
This research was conducted to evaluate apple snails as a source of fatty acids in Alabio duck feed. There are 180 female Alabio ducks, 22 weeks old, placed in 9 levels of using apple snails in feed R0 (control), R1 (2.5% swampy apple snails + basal feed), R2 (5% swampy apple snails + basal feed), R3 (7.5%, 2.5% swampy apple snails + basal feed), R4 (10% swampy apple snails + basal feed), R5 (2.5% tidal swampy apple snails + basal feed), R6 (5% tidal swampy apple snails + basal feed), R7 (7.5%, 2.5% tidal swampy apple snails + basal feed) and R8 (10% tidal swampy apple snails + basal feed), which are arranged based on a Completely Randomized Design with 4 replications. The variables that are measured were carcass weight, feed conversion, egg production, blood cholesterol profile (triglycerides, LDL, HDL and cholesterol), as well as meat and egg cholesterol. The research results reveal that using apple snails in Alabio duck feed has increase significantly (p<0.05) egg production, feed conversion, as well as a reduction in LDL level, meat cholesterol and egg cholesterol. However, no significant difference (p>0.05) was observed towards carcass weight, abdominal fat, triglycerides, HDL and blood cholesterol. A subsequent test is done with a Duncan Multiple Range Test to show that using at least 5% of swampy apple snails produce the highest egg production with the lowest meat and egg cholesterol levels.